The United States and the Green Movement in Iran: A Study on Public Diplomacy-based Direct and Indirect Engagement - M., Shibi Kiran (The journal of contemporary issues in business and government, 2021)
The foreign policy of George W. Bush towards Iran and its connection with the 2009 Green Movement in the country is not a broadly studied area in international relations. Different scholars have emphasized various aspects of his policy, hence there is no consensus on its exact nature. Though some of them have made references to the policy of regime change, various aspects related to it including the manner and details of implementation are not fully explored. Apart from that, public diplomacy played a crucial role in the Green Movement as part of the United States’ (U.S.) policy. In the context of public diplomacy, direct and indirect engagement was used to influence public opinion in Iran. This paper explores the policy of regime change taken by the US towards Iran which resulted in the green movement, and the role that direct and indirect engagement played to facilitate it as part of public diplomacy.